An Analysis of Figurative Language in Santa Esmeralda’s Song Lyrics Entitled You’re My Everything - Sukmono Bayu Adhi (Universitas Teknokrat Indonesia, 2022)
This study aims to analyze the figurative language and its meaning contained in the lyrics of the song